“El ají páprika (capsicum annuum L.) como alternativa de cultivo en la región San Martín” - Arévalo Rengifo, Juan Carlos (2010)
This engineering report called ''The paprika pepper (Capsicum annuum) as an alternativa crop in the region San Martin" was developed taking into account regional issues of rice monoculture and give an annual crop alternativa for farmers who have areas produds not take advantage to 100% if sowed cocoa, coffee or other permanent species. lt collects and analyzes information from the producers of paprika valleys of Peru and contrasted with data obtained from sorne experiences of this crop in the San Martin region, where Perhuate and Rioja the places where the crop development. The potential of this crop in Peru are good for the climate, soil, and no seasonal planting and harvesting. Given that Peru is the top global export of paprika, second only to China and India for its large seed size. Peru is having no seasonal planting and harvesting can be tailored according to the market, where there is scarce due to the non-produciion of large producers like China and India and sell the product at better prices. San Martin falls in this group far having a climate stations and air unmarked best crops in soil. Moreover San Martín is a non-endemic area of plant pathology crop problems, which allows more efficient agronomic management and less production costs. The fresh regional performance were equal to or better than the national average, but the relationship with the production of dry post-harvest were poor where they lost nearly 40% of product due to decay due to constant rains and besides not have infrastructure and drying equipment. Given that this report highlights the advantages of the San Martín region in the cultivation of paprika both yield, quality, market and so on.